Period-Adding Structures in the Parameter-Space of a Driven Josephson Junction - Rech P.C.* (2015)
© 2015 World Scientific Publishing Company.Two-dimensional parameter-space diagrams related to a driven Josephson junction are reported. Three cases are considered, namely those involving the external direct current as one of the parameters. Typical periodic structures embedded in a chaotic region are observed in all diagrams, organized in different ways: (i) As structures with a similar shape to the Arnold tongues of the circle map, in period-adding sequences, and (ii) as structures with other shapes, in arrangements including two mixed sets of period-adding sequences.